NICOLE ORESME ON MOTION AND THE ATOMIZATION OF THE CONTINUUM. - Debroise, Philippe (Revista Española de Filosofía Medieval, 2022)
As Aristotle classically defined it, continuity is the property of being infinitely divisible into everdivisible parts. How has this conception been affected by the process of mathematization of motion during the 14th century? This paper focuses on Nicole Oresme, who extensively commented on Aristotle's Physics, but also made decisive contributions to the mathematics of motion. Oresme's attitude about continuity seems ambivalent: on the one hand, he never really departs from Aristotle's conception, but on the other hand, he uses it in a completely new way in his mathematics, particularly in his Questions on Euclidean geometry, a tantamount way to an atomization of motion. If the fluxus theory of natural motion involves that continuity is an essential property of real motion, defined as a res successiva, the ontological and mathematical structure of this continuity implies that continuum is in some way "composed" of an infinite number of indivisibles. In fact, Oresme's analysis opened the path to a completely new kind of mathematical continuity.